Modernising the agricultural sector and stabilising the agricultural markets in budgetary expenditures in Poland in the years 1997-2011 = Modernizacja sektora rolnego a stabilizacja rynków rolnych w wydatkach budżetowych Polski w latach 1997-2011 - Czyżewski, Andrzej; Matuszczak, Anna (Zielona Góra: Faculty of Economics and Management Press)
The purpose of the article was to evaluate the budgetary expenditure related to the modernization of the agricultural sector and stabilization of agricultural markets, which are implemented in the framework of the common agricultural policy by two paying agencies. Research related to changes in share of spending on activities of the Agricultural Market Agency (AMA) and the Agency for Restructuring and Modernisation of Agriculture (ARMA) in total budget expenditure in the long run, ie in the years 1996-2011 (16 years) with honors from the period before and after accession to the EU.
Keywords: rolnictwo; modernizacja; rynki rolne; wydatki budżetowe; agriculture; modernisation; agricultural markets; budgetary expenditures